Pharma TARP: A Troubled Asset Relief Program for Novel, Abandoned Projects in the Pharmaceutical Industry - Tamas Bartfai; Graham Vaughan Lees (The Scientific World Journal)
Within days of each other, Pfizer, Merck, and GlaxoSmithKline announced that they will focus on a few therapeutic areas only and abandon others entirely. Pfizer alone will close well over a hundred drug development projects that have reached two-thirds of the way to launch. The programs are deemed to be too risky and not lucrative enough for Big Pharma in the current climate. Society has a real need for the drugs that are no longer going to be developed for, among others, drug-resistant epilepsy, neuropathic and cancer pain, type-2 diabetes, obesity, and schizophrenia. The authors propose a radical response by the U.S. government and the National Institutes of Health to rescue these abandoned projects, and to continue selected programs for drug approval by the U.S. Food and Drug Administration and the European Medicines Agency. The investment required is small compared to the Troubled Asset Relief Program bank bail out, but the return on investment in financial terms and in satisfying societal needs makes this proposal attractive.